Dopaminergic regulation of hippocampal plasticity, learning, and memory - Tsetsenis, Theodoros; Broussard, John I.; Dani, John A. (Frontiers in Behavioral Neuroscience, 2023)
Abstract The hippocampus is responsible for encoding behavioral episodes into short-term and long-term memory. The circuits that mediate these processes are subject to neuromodulation, which involves regulation of synaptic plasticity and local neuronal excitability. In this review, we present evidence to demonstrate the influence of dopaminergic neuromodulation on hippocampus-dependent memory, and we address the controversy surrounding the source of dopamine innervation. First, we summarize historical and recent retrograde and anterograde anatomical tracing studies of direct dopaminergic projections from the ventral tegmental area and discuss dopamine release from the adrenergic locus coeruleus. Then, we present evidence of dopaminergic modulation of synaptic plasticity in the hippocampus. Plasticity mechanisms are examined in brain slices and in recordings from in vivo neuronal populations in freely moving rodents. Finally, we review pharmacological, genetic, and circuitry research that demonstrates the importance of dopamine release for learning and memory tasks while dissociating anatomically distinct populations of direct dopaminergic inputs.